2015
DOI: 10.1016/j.molp.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of the BRI1 Receptor and its Regulation by Membrane Microdomains in Living Arabidopsis Cells

Abstract: The major brassinosteroid (BR) receptor of Arabidopsis BRASSINOSTEROID INSENSITIVE1 (BRI1) plays fundamental roles in BR signaling, but the molecular mechanisms underlying the effects of BR on BRI1 internalization and assembly state remain unclear. Here, we applied variable angle total internal reflection fluorescence microscopy and fluorescence cross-correlation spectroscopy to analyze the dynamics of GFP-tagged BRI1. We found that, in response to BR, the degree of co-localization of BRI1-GFP with AtFlot1-mCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
135
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 80 publications
19
135
4
Order By: Relevance
“…Further analysis employing a one-dimensional Gaussian fit of the fluorescence intensity over the cross section of the PM suggests that most of the observed mobility in the elongation zone is due to replenishment from internal receptor pools (S7 Fig). In a similar study by Wang and coworkers [19], BRI1-GFP was expressed under its native promoter in Col 0 background and a diffusion coefficient of 8.8x10 -3 μm 2 *s -1 was found, which is in similar range to our observations in meristem cells. Taken together, our VAEM and FRAP data suggest that both BRI1 and SERK3/BAK1 receptors are distributed in PM nanoclusters, which are largely immobile and contain only a limited number of BRI1 and SERK3/BAK1 receptors.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Further analysis employing a one-dimensional Gaussian fit of the fluorescence intensity over the cross section of the PM suggests that most of the observed mobility in the elongation zone is due to replenishment from internal receptor pools (S7 Fig). In a similar study by Wang and coworkers [19], BRI1-GFP was expressed under its native promoter in Col 0 background and a diffusion coefficient of 8.8x10 -3 μm 2 *s -1 was found, which is in similar range to our observations in meristem cells. Taken together, our VAEM and FRAP data suggest that both BRI1 and SERK3/BAK1 receptors are distributed in PM nanoclusters, which are largely immobile and contain only a limited number of BRI1 and SERK3/BAK1 receptors.…”
Section: Resultssupporting
confidence: 90%
“…This is conjunction with the work of Wang and coworkers in which a diffusion coefficient of BRI1-GFP of (8.8 ± 0.6) 10 −3 μm 2 *s -1 was found [19]. As in the case of EGFR, animal receptor nanoclusters are thought to be confined by the cortical actin filament network and cholesterol rich domains [43].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The ER marker RFP–HDEL and cyan fluorescent protein (CFP)–HDEL (Lee et al , 2013; Wang et al , 2014), the Golgi marker sialyltransferase (ST)–RFP (Renna et al , 2005; Schoberer et al , 2010), the early endosome marker CLC–mCherry (Wang et al , 2013; Wang et al , 2015), the microtubule marker MBD-MAP4 (microtubule-binding domain of microtubule-associated protein 4)–DsRed (Marc et al , 1998; Granger and Cyr, 2001), and the actin maker ABD2–mCherry (Voigt et al , 2005) were described in the indicated reports.…”
Section: Methodsmentioning
confidence: 99%